Equity, vulnerability and childhood immunization in Kenya and Uganda. A review of policy documents protocol - Owino, E; Mafigiri, D; Kamuya, D; Jones, C; Chi, P (National Institute for Health and Care Research, 2023)
Introduction Inequities in access and uptake of vaccines remains to be a challenge to the full realization of benefits they stand to offer. In the case of childhood immunization, improved full immunization coverage has been witnessed globally in the past decades but countries in sub-Saharan Africa have registered slow progress, with variations between/within countries. This has been attributed to several challenges/vulnerability factors. Consequently, current global efforts to promote access to immunization have focused on the issue of equity, which is now a strategic priority in key international policy documents such as the World Health Organization immunization agenda 2030 among others. It is therefore important to understand the context and efforts being made by individual countries to realize equity. We plan to undertake a systematic policy document review to understand the immunization context in Kenya and Uganda by examining the extent to which equity and vulnerability issues are framed and addressed in key health sector and policy documents in both countries. Methods The systematic review will focus on key health sector and immunization policy documents in Uganda and Kenya between 2000 and 2023. Documents in the English language will be reviewed. Data sources will include official ministry of health websites for each country, websites of key international organizations working on immunization, general google searches and requesting for relevant documents from immunization stakeholders and officials in both countries. Data synthesis will follow a deductive and inductive approach. Findings will be presented in a descriptive format and in line with review objectives. Discussion We will assess the extent to which equity and vulnerability issues are included and how they are defined in the health sector and immunization policy documents. In addition, the review will examine strategies proposed, planned and/or implemented to promote equitable access and uptake of immunization services in the two countries.